DEVELOPMENT ADVANTAGES OF CASHLESS PAYMENTS IN THE PAYMENT SYSTEM OF UZBEKISTAN - Narmamatov, Ixtiyor (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article identifies problems associated with improving the practice of using forms of cashless payments in the Republic of Uzbekistan and developed scientific proposals aimed at solving these problems. The transition to electronic payments improves the efficiency of the economy, reduces cash, improves financial transparency, promotes financial inclusion, promotes the digital economy, reduces costs and provides convenience for users.